Challenge of free economic zones in Central and Eastern Europe: international perspectives (United Nations New YorkUS, 1991)
Deals with the role of free economic zones in development, particularly the function of those in the USSR; procedures for establishing regulation and administering such zones; institutional and economic issues related to the zones; domestic and international linkages; alternatives for dealing with foreign exchange in the absence of the convertibility of the rouble; and ways and means of promoting free economic zones to both domestic and foreign investors. Also reviews the performance of a number of free economic zones in various countries.
Bibliography: p.429-435